Hybrid passive damping filter of single-phase grid-tied PV-micro inverter - Aamara, Fouzey Salem; Balachandran, Praveen Kumar; Yusof, Yushaizad; Radzi, Mohd Amran Moohd; Zainuri, Muhammad Ammirrul Atiqi Mohd (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Photovoltaic (PV) microinverter with inductor-capacitor-inductor (LCL) filter has many advantages, but it has resonance with the grid current situation could potentially lead to stability issues to enhance the power quality; reducing the grid current total harmonic distortion (THD) is crucial, as it currently exceeds the limits set by the IEEE power system standards. That improves the hybrid passive damping filter topology, which can perform better than the LCL output filter. The damping filter is effective in alleviating the resonance peak occurring at the resonant frequency of the LCL filter, thereby minimizing voltage overshoots and ringing; by utilizing smaller capacitors, the damping filter enhances system reliability while also reducing the cost and size of the LCL filter. Simulation research has been done to propose a hybrid passive damping filter using MATLAB/Simulink tools under both conditions, the steady-state and dynamic response. Simulation results indicate that the passive damping filter works well under both conditions with low THD compared to LCL and H-Bridge (H-B) filters. Many methods are used to solve the problem of high THD grid current. The passive damping filter method simplifies the PV microinverter. This study aims to achieve a high-efficiency PV microinverter by minimizing total power losses.